Conducting international research and service collaborations : tips, threats, and triumphs - McCall, Robert B., 1940-; Groark, Christina J. (New York, NY : Routledge, 2022)
Conducting International Research and Service Collaborations: Tips, Threats, and Triumphs provides academic researchers,as well as non-profit and privateprofessionals, with much-needed guidance on how to plan, implement, and manageinternational research and intervention projects. Accessibly written and illustrated throughout with examples and case studies of projects fromRobert B. McCall and Christina J. Groark's wide-ranging anddecades-long experience of cross-border collaborations, this book outlines how to prepare for and ensure success of cross-border research projects and interventions, how to embrace unique circumstances you may encounter, and what to do if things go wrong. Each chapter covers a general domain of concerns, advice, and lessons learned in conducting international collaborative projects followed by concrete illustrations that pertain to them. Key topics covered include launching projects and working with stakeholders, travelling and living abroad, cultural considerations, planning and funding, administrative issues, dealing with crises, and successfully implementing and disseminating findings effectively. This comprehensive guide is ideal for researchers and project managers - from large, global organizations to small NGOs, human services, private industry, and other fields embarking on such projects, as well as university students and academics.
Keywords: Research -- Methodology; Research -- International cooperation; Intellectual cooperation; EDUCATION / General; EDUCATION / Experimental Methods; EDUCATION / Special Education / General